“Bottom-up” Community-Based Development : Gabon Urban Development Project - World Bank (World Bank, Washington, DC, 2012)
The Gabon Urban Development Project is being conducted through a series of pilot projects in the poorest, most densely populated neighborhoods in three cities. Reducing poverty hinges on increasing the access of the poor to employment opportunities. This requires improving infrastructure, which includes establishing water and sanitation systems, as well as creating roads, safe walkways, and transport services. This work is being carried out by local contractors and employs the local poor. The project's bottom-up approach is a key strategy for sustainability. The pilot project focuses on the construction of roads through targeted neighborhoods to improve access and create direct, complementary benefits such as services, local employment, and support for local construction companies. To increase employment of local unskilled laborers, the project uses concrete blocks for paving roads. At the community level, each targeted neighborhood provides help to identify the location and alignment of the road that would make the area more accessible. One of the criteria in the exercise is that the proposed road should not involve involuntary resettlement. Working with the assistance of NGOs, each neighborhood organizes its Community Finance Plans (CFP) around micro-projects that complement the construction of the main road. The NGOs provide technical assistance such as engineering and architectural expertise to the communities to ensure that their micro-projects are linked to the provision of local public goods and services. In addition, each micro-project must meet certain standards: that environmental conditions are improved and that no adverse environmental impact will result from implementation or construction. Local NGOs assess and certify these standards while the Ministry of Planning oversees the process. After the project is completed, it is expected that, to generate their own source of activity as advocate planners on behalf of communities, NGOs will pressure local governments to target poor communities. Targeting will include allocating appropriate budget.